Use of mHealth in Atrial Fibrillation Telemonitoring: A Literature Review - Beti Ningrum; Tuti Herawati (Journal of Nursing Care, 2023)
Management of atrial fibrillation (AF) is limited to low detection, treatment non-adherence and several other considerations, resulting in the utilization of mobile health devicesÂ  (mHealth) for comprehensive and continuous telemonitoringÂ  of atrial fibrillation. This study aims to identify the use of mHealth in atrial fibriullation telemonitoring. The reseach design is a literature review using the PRISMA method approach. Literature search used the keywords â€œmHealthâ€ and â€œtelemonitoringâ€ and â€œatrial fibrillationâ€ from the PubMed, Science Direct, Scopus and ProQuest databases, with inclusion criteria namely article on the use technology or mobile health-based applications in telemonitoring atrial fibrillation (AF), articles less than 5 years, fulltext and open access. The seven articles analyzed, six articles on the use of mHealth can be used for atrial fibrillation telemonitoring and one article shows the use of applications for educational media. Further development is needed in line with increasing needs, ease of use and technological developments in the health sector.Â Â